Гостья из будущего: фантастическая повесть / Кир Булычёв - Булычёв Кир (Школьное чтение, 2022)
Экземпляры: ф. 14 (20230321) / Инвентарный номер: 65379 / Цена: 244.00 / Авт.знак: Б 90 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6